Construction of a BAC-library for sunflower - Özdemir, Nehir; Justus Liebig University Giessen (My University, 2000)
For Sunflower (Helianthus annuus L.), one of the most important oil crops of the world, a bacterial artificial chromosome (BAC) library wasconstructed. As a plant material the restorer line RHA325 which is an open American inbred line with PET1-plasma, has got two importantgenes for sunflower that are the Pl2-gene conferring resistance to downy mildew and the restorer gene Rf1, which is responsible for fertilityrestoration in the presence of the PET1 cytoplasm. An essential prerequisite for BAC cloning is the preparation of high molecular weightDNA (HMW DNA). The most common methods for plant high-molecular-weight DNA isolation are preparations from protoplasts or nuclei.For sunflower which has a genome size of 3000 Mb, both methods for the isolation of high molecular weight DNA were successfullydeveloped using leaf material from two weeks old seedlings. Two BAC cloning vectors, pBeloBACKan and pBeloBAC11, which have anunique cloning site for EcoRI and HindIII, respectively, were tested. Because of the high transformation efficiency pBeloBAC11 was usedfor the construction of a BAC library for sunflower. Partial digestion with HindIII only needed to be optimised with regard to the amount ofrestriction endonuclease and incubation time. Size fractionation of digested DNA fragments by PFGE allowed to isolate fragmentsbetween 200 and 500 kb for BAC cloning. The current BAC library comprises 104,736 clones. A number of 179 BAC clones were picked at random and analysed by minipreparationfor estimation of the average insert size, which turned out to be 50 kb. The insert size of clones varied between 20 kb and 270 kb with themajority of clones between 40 and 60 kb. According to the average insert size, the sunflower BAC library covers a 1.7x genome equivalent.The stability of BAC inserts was demonstrated by two clones with a size of 72 and 100 kb for 11 and 12 generations. The whole BAClibrary was spotted in duplicate on four filters, each carrying 55,296 clones. Hybridisation of these filters against a cDNA clone (sf21)revealed four positive clones which is in the expected range of genome coverage. The BAC library is now available for map-based cloning approaches of the resistance gene Pl2 and the restorer gene Rf1 which require alarge insert DNA library for chromosome walking and chromosome landing. In addition, the constructed BAC library represents an essentialtool for any further genome analyses e.g. fluorescence in situ hybridisation (FISH) in sunflower.
Keywords: Bac-Library sunflower; ddc:630